2017
DOI: 10.20471/acc.2017.56.04.05
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relationship of Changes in Visual Field Indices with Quadrant and Average Retinal Nerve Fiber Layer Thickness in the Eyes with Exfoliation

Abstract: The progressive nature of glaucoma suggests it should be possible to detect structural changes such as retinal nerve fiber layer (RNFL) thickness loss before the condition becomes clinically apparent with visual field (VF) impairment. Therefore, the aim was to analyze RNFL thickness and VF changes in study groups with unilateral exfoliation syndrome (XFS), bilateral XFS and bilateral exfoliative glaucoma (XFG), and compare it with controls. The study included 114 subjects (228 eyes) divided into 4 groups accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…[ 7 10 ] Untreated perinatal depression may result in adverse obstetric outcomes and is a risk factor for poor maternal health, inadequate prenatal care, and postnatal depression. [ 10 , 11 ] In addition to the potential negative impact on pregnancy outcomes, perinatal depression is associated with disrupted maternal-infant bonding, increased irritability, and decreased activity. Children born to depressed mothers are at risk for delayed cognitive and language development, lower IQ, and increased prevalence of psychiatric and emotional problems.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 10 ] Untreated perinatal depression may result in adverse obstetric outcomes and is a risk factor for poor maternal health, inadequate prenatal care, and postnatal depression. [ 10 , 11 ] In addition to the potential negative impact on pregnancy outcomes, perinatal depression is associated with disrupted maternal-infant bonding, increased irritability, and decreased activity. Children born to depressed mothers are at risk for delayed cognitive and language development, lower IQ, and increased prevalence of psychiatric and emotional problems.…”
Section: Introductionmentioning
confidence: 99%
“…The term ‘anxiety’ may encompass a wide variety of constructs ranging from clinical diagnosis to self-report measures of symptoms to more general measures of stress [ 1 ]. Elevated symptoms of anxiety have been reported in 15–16% of pregnant women and in 8–9% of postpartum women [ 2 ]. Other reports have shown that the prevalence of prenatal anxiety has been estimated in 25% during the first trimester and 21% during the third trimester of pregnancy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 A study in Croatia reported 17% prevalence of high anxiety occurring immediately after childbirth, 20% at 6 weeks post partum and the comorbidity of anxiety and PPD was 75%. 25 Characteristics of anxiety include excessive worry that lasts, accompanied by restlessness, fatigue, poor concentration, muscle tension and sleep disturbance. 9 Other symptoms include excessive worry, feeling nervous or on the edge, inability to stop or control worrying, having troubles relaxing, feeling easily irritable or annoyed and feeling awful as if something bad is going to happen.…”
Section: Open Accessmentioning
confidence: 99%
“…Sociodemographic information and possible risk factors of the participants will be captured via a set of validated questionnaires, postpartum depression (PPD) will be measured using the Edinburgh Postpartum Depression Scale questionnaire and general depressive symptoms, anxiety and stress will be measured using the 21-item Depression, Anxiety and Stress Scale. Data analysis will be conducted using SPSS V. 25.0 (IBM). Besides descriptive statistics, multivariable regression analyses will be done to identify possible risk factors and their independent associations with depression (PPD and general depressive symptoms, combined and separately), anxiety and stress.…”
mentioning
confidence: 99%